Jornal da Exystêncya: conjurando terrytóryos férteys em tempos de fym de mundo - Seabra, Carú Ynymagynável de Paula; Ribeiro, Carú de Paula Seabra Moreira (2022)
The Journal of Existence aims to inhabit the crossing of the colonial, capitalistic, racializing linear time. It manifests itself under an irreducible ethical and political commitment that the clinic prescinds: the conjuration of what prevents the pulse of life from prevailing in the conduction of existence. A clinic radically committed to the creation of possibilities for dignified lives, seeking to guarantee autonomy, even if (and especially) in contexts of extreme violence and psychic suffering. In this sense, this dissertation is inscribed in the field of distinct theories and practices of Psychology that seek to confront the choking points of the present, contributing to its transformation - in this case, in the specific plane of subjectivity